Quantitative Proteomics Reveals the Beneficial Effects of Low Glucose on Neuronal Cell Survival in an in vitro Ischemic Penumbral Model - Li, Hua; Kittur, Farooqahmed S.; Hung, Chiu-Yueh; Li, P. Andy; Ge, Xinghong; Sane, David C.; Xie, Jiahua (Frontiers in Cellular Neuroscience, 2020)
Understanding proteomic changes in the ischemic penumbra is crucial to rescue those salvageable cells and reduce the damage of ischemic stroke. Since the penumbra region is dynamic with heterogeneous cells/tissues, tissue sampling from animal models of stroke for molecular study is a challenge. In this study, cultured hippocampal cells under hypoxia treatment for 17.5 h with 0.69 mM low glucose (H+LG) could mimic ischemic penumbral cells since they had much higher cell viability and viable cell number compared to hypoxia without glucose (H-G) treatment. To validate established cell-based ischemic penumbral model and understand the beneficial effects of low glucose (LG), quantitative proteomics analysis was performed on H+LG, H-G, and normoxia with normal 22 mM glucose (N+G) treated cells. We identified 459 differentially abundant proteins (DAPs) between H-G and N+G, and further identified 115 DAPs between H+LG and H-G. Analysis of 115 DAPs revealed that LG promotes cell survival by activating HIF1α to enhance glycolysis; preventing the dysregulations of extracellular matrix remodeling, cell cycle and division, and antioxidant and detoxification; as well as attenuating inflammatory reaction response, protein synthesis and neurotransmission activity. Our results demonstrated that this established cell-based system closely mimics penumbral conditions and can be used for molecular studies.